Sistem Bagi Hasil Sebagai Pondasi Stabilitas Moneter Syariah - Putria, Uus; Nasrudin, Nasrudin; Nursari, Nina (ISLAMICA, 2022)
The purpose of this study is to identify a Profit-Loss Sharing System through skim mudharabah, musyarakah or in agriculture called muzara'ah as a solution to replace flowers. This research uses an empirical sociological approach method that is descriptive analysis with the use of qualitative data as the type of research and library research as one of the data collection techniques. This study concluded that: First, this form of business, is seen as fair compared to the form of business in conventional economics, because of the profits and losses that occur, all parties involved have the same rights to the business results obtained. Second, monetary policy determines a country's economic success, which is in line with the objectives of Islamic economic policy, namely maintaining and maintaining the country's economic stability. Third, policy-making measures are taken by policymakers in accordance with sharia principles, namely the profit-sharing system. Where sharia principles do not allow guarantees against face value or rate return (interest rate).